The Effect of Gibberellic Acid and Brassinolide and Their Interaction on Some Chemical Characteristics of Plant Dill Anethum graveolens L. - Al-Shimary, Mahir Zeki Faysal; Al-Jboury, Wael shakir Hameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment for the growing season. 2015-2016 to study the effect of gibberellic acid at concentrations (0 and 50)mgL-1 and BL at five concentrations (0, 0.5 ,1 ,2 and 3)mg.L-1 and their interaction on some chemical characteristics for Dill plant . The experiment was designed according to Randomized Complete Block Design (RCBD) with three replicates per treatment, using less significant difference at the level of probability (0.05) , the results showed the following:- 1- The effect of brassinolide with it,s concentrations led to obtain on a significant increase in all the studied characteristics, so the superiority of the concentration of 2 mg.L -1 of brassinolide in each of nitrogen, potassium and protein, And the superiority of concentration with 1 mg .L -1 of brassinolide in phosphate.  2- The effect of gibberellic acid with it,s two concentrations led to obtain on a significant increase in all the studied characteristics and the highest in of the concentrate at 50 mg.L -1 in two local and dutch varieties. 3-The all bilateral interactions had a significant effect on all the studies characteristics  with superiority of the treatment (2 from brassinolide ,50 from gibberellic acid) mg.L-1 in the ratio of nitrogen, potassium and protein, the treatment of (1 from brassinolide,50 from gibberellic acid) mg.L-1 in the ratio of phosphate, and the superiority of dutch variety in the ratio of nitrogen, potassium and protein, and the superiority of the local variety in the ratio of phosphate.  4- The triple interactions led to obtain a significant increase in only phosphate ratio, while the nitrogen ratio, potassium and the protein not with triple interactions among the study of significant factors.